Tailored macro-pores during the formation of C/C-SiC via liquid phase pyrolysis. Issue 5 (May 2021) - Flauder, Stefan; Langhof, Nico; Krenkel, Walter
Abstract: The synthesis of C/C-SiC via liquid silicon infiltration (LSI) with thermoplastic carbon precursors can lead to the formation of macropores in the C/C state. The macro-pore pattern formation can be controlled and used as a new level in microstructure for ceramic matrix composites. The pore formation occurs in the CFRP state with the remelting of the thermoplastic matrix and can be fixed to the C/C state after liquid phase pyrolysis. The macro-pores are primarily induced by a non-linear elastic recovery of the fiber preform and not via gas formation and release during pyrolysis. The formation of the macroporosity is described and explained. These pores can be tailored by process control in size and shape. The pore shapes can vary from isolated spherical pores to an interconnected tube like macro-pore network. The relationship between starting setting variables of the fiber preform, the process conditions, and the resulting structure are discussed.